Review of Transsexual Marriage Under Indonesian Civil Law - Febriyanti, Wiwin Dwi Ratna; Azis Putri, Shinta Maharani (Universitas Negeri Gorontalo, 2024)
This research was conducted to find out about the position of transsexual marriage according to state law and the legal consequences of transsexual marriage in Indonesian civil law. This research is a doctrinal/normative legal research. The types of approaches used are statute, case, and conceptual approaches. Based on this research, it is concluded that marriages conducted by transsexuals are declared valid because they have obtained a court decision regarding changes in gender status and have changed population administration data at the Population and Civil Registration Office (Disdukcapil) so that they can marry legally according to the provisions of positive law in Indonesia. So, it has legal consequences for legal relations between husband and wife, the formation of marital property, the position and status of children, and inheritance relations.